DIGITAL MARKETING (Conferencea, 2023)
The purpose of this study is to focus on digital marketing in Uzbekistan and in other development countries. The marketing servises are done through the use of digital technology, primarily the Internet but also including mobile devices, display advertising, and any other digital medium. The evolution of digital marketing since the 1990s and 2000s, technology has changed how companies and brands use it for marketing. Digital marketing efforts are becoming more common and effective as digital platforms are integrated into everyday life and marketing strategies and as individuals utilize digital gadgets rather than go to physical stores. This essay primarily focuses on a conceptual knowledge of digital marketing, how it benefits modern businesses, and a few real-world instances.